Cystic abdominal masses in children: a pictorial essay - Onur, Mehmet Ruhi; Bakal, Unal; Kocakoc, Ercan; Tartar, Tugay; Kazez, Ahmet (Elsevier Science Inc, 2013)
Cystic abdominal masses in children are not an infrequently encountered condition of childhood. These lesions usually present with large size and mimick each other with similar presenting symptoms. Imaging examinations have an important role to determine the type of the cystic abdominal masses, which is crucial for management of patients and presurgical planning. In this pictorial essay, we summarized the imaging features of common cystic abdominal masses of children, including cystic lesions arising from liver, biliary ducts, kidney, pancreas, bowel, ovary, mesentery, and miscellaneous tissues. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Children; Abdomen; Cysts; Imaging; Diagnosis; Treatment